PENGARUH PERSEPSI PROFESI GURU DAN LINGKUNGAN KELUARGA MELALUI EFIKASI DIRI TERHADAP MINAT MENJADI GURU - Febrianti, Putri Lishia Irfan; Noviani, Leny; Octoria, Dini (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
The background of this research is the low number of graduates from Economics Education, Accounting Education, and Office Administration Education who have careers as teachers. Less than 50% of total graduates pursue careers as teachers. The aim of education program is to prepare graduates to become professional teachers. Interest in becoming a teacher is motivated by various factors, including perceptions of the teaching profession, family environment, and self-efficacy. This research aims to determine how perceptions of the teaching profession and family environment influence the interest in becoming a teacher, mediated by self-efficacy. This research uses quantitative research with data analysis techniques, namely path analysis. The population used in this research was students of Economic Education, Accounting Education, and Office Administration Education FKIP UNS class 2019-2020. The number of samples used was 220 students. Data collection in this research used a questionnaire distributed online via Google form. The results of this research show that student perceptions of the teaching profession has a positive and significant influence on their interest in becoming teachers. Family environment has a positive and significant influence on interest in becoming a teacher. Self-efficacy has a positive and significant influence on interest in becoming a teacher. Self-efficacy can mediate the teacher's professional perception of interest in becoming a teacher. Self-efficacy can mediate the family environment on interest in becoming a teacher.